Consumer Ethnocentrism and Attitude Toward Domestic Product in Pekanbaru - Julina Julina; Bambang Kariyawan (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
The purpose of this research is to discover high school student ethnocentrism and their attitude toward domestic product. Identifying these factors are very important for marketers in design their marketing program. Based on consumer ethnocentrism questionnaire (CETSCALE) developed by Shimp and Sharma (1987), 17 questions were given to the student from one private high school in Pekanbaru City, Riau Province. Moreover, question about their attitude, preference, and the reason to choose domestic product also being questioned. About 118 students participated in this study. The data collected was analyzed through qualitative and quantitative method. The result showed that this study provides support for the CETSCALE’s reliability and validity. Mean score on the CETSCALE is 57.20, which is indicating a moderate level. From the question about country of origin, approximately 60.2% respondents pay attention to the product country of origin. In relation to the price, 55.1% would buy the domestic product if the price between the domestic and foreign product is the same. On the other situation 71.2% respondent would buy the domestic product if the price is cheaper, contrary to only 23.7 % respondent that keep buying domestic product even the price is higher. It is important to note that even they have high ethnocentrism score, not all of them willing to buy domestic product when the price is higher. We also gave them opened question asking about what kind of product and services they prefer domestic made. Nearly 50% mentioned clothes or dress and many respondents refer to specific kind of clothes or motive such as Batik. Food is chosen by at least 66% respondent as domestic product they prefer. The most reasons are the cheap prices, same quality, delicious taste for food, and proud to consume the domestic product. We may conclude that respondent were ethnocentrism at certain product but still considering the price to make a buying decision.